Te Pā: A wellbeing initiative on a major roading construction project. - Heta, Hemi; Kennedy, Barbara; Gardner, Dianne (New Zealand Journal of Health and Safety Practice, 2024)
Purpose. Due to the significant challenges to employee wellbeing in the construction industry, a major roading project in New Zealand implemented a wellbeing programme based on holistic health frameworks. A description, rationale and outline of the wellbeing programme are presented. An independent evaluation of the wellbeing programme took place in 2023. Design. Data from interviews, a focus group, surveys, and the OnLocation app were analysed to examine participants’ perspectives on the programme, and to establish whether the programme was effective and how it could be improved. Findings. The majority of staff reported that they had experienced enhanced wellbeing since joining the project, and spoke positively about the programme. A small number of participants felt the project still had elements of the ‘old’ construction culture including a focus on productivity over people, but most felt the wellbeing programme had made substantial progress toward changing the construction culture. Suggested improvements included a perceived need for more resources, for members of the wellbeing team to be present onsite more often, and more training for onsite managers in workplace wellbeing. Originality. A holistic approach to wellbeing has rarely been taken in the construction industry. This project was based on indigenous New Zealand Māori perspectives on wellbeing. Evaluation showed that it was positively valued by both Māori and non-Māori participants. This indicates that, although some details are specific to New Zealand, the model itself, its supporting framework and approach can be generalised to other contexts.